2014
DOI: 10.1186/1472-6882-14-487
|View full text |Cite
|
Sign up to set email alerts
|

The induction of activating transcription factor 3 (ATF3) contributes to anti-cancer activity of Abeliophyllum distichum Nakai in human colorectal cancer cells

Abstract: BackgroundRecently, Abeliophyllum distichum Nakai (A. distichum) has been reported to exert the inhibitory effect on angiotensin converting enzyme. However, no specific pharmacological effects from A. distichum have been described. We performed in vitro study to evaluate anti-cancer properties of A. distichum and then elucidate the potential mechanisms.MethodsCell viability was measured by MTT assay. ATF3 expression level was evaluated by Western blot or RT-PCR and ATF3 transcriptional activity was determined … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 25 publications
(30 reference statements)
1
13
0
Order By: Relevance
“…*P < .05, compared with NC or siNC group Nakai could resist cancer by up-regulating ATF3 repression in colorectal cancer. 19 In our study, differentially expressed genes were analysed by microarray. As it was found out, ATF3 expression was significantly higher in breast cancer tissues and cells after radiation therapy.…”
Section: Discussionmentioning
confidence: 99%
“…*P < .05, compared with NC or siNC group Nakai could resist cancer by up-regulating ATF3 repression in colorectal cancer. 19 In our study, differentially expressed genes were analysed by microarray. As it was found out, ATF3 expression was significantly higher in breast cancer tissues and cells after radiation therapy.…”
Section: Discussionmentioning
confidence: 99%
“…However, gene expression analysis indicated that AL induces cell death via activation of the extrinsic pathway ( Figure 3 B). In human colorectal cancer cells, the ethyl acetate fraction of 80% methanol extract obtained from the plant parts of A. distichum including the flower, leaf, and branch induced transcriptional activation of activating transcription factor 3 (ATF3), resulting in apoptosis induction [ 12 ]. Various human cancers, including liver cancer, prostate cancer, colon cancer, and multiple myeloma, exhibit a low level of ATF3 expression [ 36 , 37 , 38 , 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Abeliophyllum distichum Nakai is a deciduous flowering shrub, a monotypic genus with a single species of deciduous shrub in the olive family [ 6 ]. Although A. distichum has been used as a horticultural crop because of its ornamental value, the pharmaceutical properties of A. distichum extracts have been recently revealed, such as the anti-inflammatory effect [ 7 ], antioxidant activity [ 6 ], DNA damage inhibition [ 8 ], whitening property [ 9 ], anti-diabetic effect by inhibiting aldose reductase [ 10 ], antihypertensive activity [ 11 ], and anti-proliferative activity against human colorectal cancer cells [ 12 ]. Additionally, phytochemical investigations of A. distichum have revealed the presence of multiple active ingredients, such as acteoside, eutigoside B, isoacteoside, rutin, cornoside, hirsutrin, chlorogenic acid, caffeic acid, gentisic acid, ferulic acid, and quercetin [ 6 , 10 , 11 ], indicating the potential of A. distichum to be developed as a phytomedicine and a source to develop anti-melanoma agents, although no systematic study exists regarding the anti-melanoma action of A. distichum .…”
Section: Introductionmentioning
confidence: 99%
“…Activating transcription factor 3 (ATF3) is a key transcription factor in cellular stress responses, with different expression levels and functions in different tissues (16). It has been shown that ATF3 can be either an oncogene or a tumor suppressor gene depending on the type of tumor (17)(18)(19)(20)(21). For instance, ATF3 was found to be down-regulated in esophageal squamous cell carcinoma (ESCC) lesions, and forced expression of ATF3 led to decreased growth and invasive properties of ESCC cells in vitro and in vivo through regulation of MDM2 expression (22).…”
Section: Introductionmentioning
confidence: 99%